1995
DOI: 10.1007/bf00731867
|View full text |Cite
|
Sign up to set email alerts
|

Localization of peanut (Arachis hypogaea) root lectin (PRA II) on root surface and its biological significance

Abstract: The glucose-specific peanut root lectin, PRA II, is localized on the surface of 7-day-old peanut seedling root and in root cortical parenchymatous cells. The lectin is eluted from intact roots upon washing with buffer containing glucose. Rabbit erythrocytes bind to the root surface and the cortical cells; the binding is inhibited by antibodies raised against PRA II, peanut-specific Rhizobium cells and by glucose. Lipopolysaccharides isolated from host-specific Rhizobium strain inhibit the haemagglutinating act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Research on Trifoliin A largely contributed to the legume lectin story (Dazzo and Truchet, 1983), but this protein and the corresponding gene await further characterization. Other interesting lectins are the 4-methyl-glucuronic acidbinding lectin from soybean, which may interact with surface saccharides from Bvadyrhizobium elkani (DombrinkKurtzman et al, 1983), and PRAII, a Glc-binding lectin from the roots of peanut, which specifically agglutinates peanut rhizobia (Kalsi et al, 1995).…”
Section: Other Root Lectinsmentioning
confidence: 99%
“…Research on Trifoliin A largely contributed to the legume lectin story (Dazzo and Truchet, 1983), but this protein and the corresponding gene await further characterization. Other interesting lectins are the 4-methyl-glucuronic acidbinding lectin from soybean, which may interact with surface saccharides from Bvadyrhizobium elkani (DombrinkKurtzman et al, 1983), and PRAII, a Glc-binding lectin from the roots of peanut, which specifically agglutinates peanut rhizobia (Kalsi et al, 1995).…”
Section: Other Root Lectinsmentioning
confidence: 99%
“…triJolii suggest LPS to be strain specific antigenic determinants (13). Our recent studies on LPS isolated from the peanut specific strains indicated that these molecules interact specifically with the peanut root lectin PRA II (6,14,15). The diversity in composition, structure and antigenic determinants of the LPS from various rhizobia and our studies on interaction of LPS with PRAII paved the way to characterize the LPS from Bradyrhizobium specific for the peanut plant.…”
mentioning
confidence: 99%
“…In peanut roots, lectins have been found that bind α-as well as β-glycosidically linked glucose residues [Kalsi et al, 1992[Kalsi et al, , 1995Das et al, 1994;Singh and Das, 1994;Singh et al, 1997]. This is in marked contrast to other leguminous lectins which bind glucose and mannose but exclusively their a-anomeric forms.…”
Section: Extrinsic Rolesmentioning
confidence: 41%